2011
DOI: 10.1111/j.1600-0684.2011.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased inherent intestinal granzyme B expression may be associated with SIV pathogenesis in Asian non-human primates

Abstract: Background Unlike Asian non-human primates, chronically SIV-infected African non-human primates (NHP) display a non-pathogenic disease course. The different outcomes may be related to the development of an SIV-mediated breach of the intestinal mucosa in the Asian species that is absent in the African animals. Methods To examine possible mechanisms that could lead to the gut breach, we determined whether the colonic lamina propria (LP) of SIV-naïve Asian monkeys contained more granzyme B (GrB) producing CD4 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Cytotoxic T cells confer host cell immunity against viral pathogens through release of perforin and granzyme (particularly GrzB) from cytolytic granules [19][20][21]. While HIV-specific defects in CTL activity have been reported to occur in ART receiving HIV-1-infected individuals [47], we wanted to evaluate if, as a consequence of other systemic T cell dysfunction such as elevated activation and T reg frequency, increased cytotoxic potential was observed and influenced by virological suppression in all three infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic T cells confer host cell immunity against viral pathogens through release of perforin and granzyme (particularly GrzB) from cytolytic granules [19][20][21]. While HIV-specific defects in CTL activity have been reported to occur in ART receiving HIV-1-infected individuals [47], we wanted to evaluate if, as a consequence of other systemic T cell dysfunction such as elevated activation and T reg frequency, increased cytotoxic potential was observed and influenced by virological suppression in all three infections.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this study we sought to investigate impact of ART on immune restoration by assessing systemic T cell functions and HIV‐specific T cell responses, particularly in HIV‐2 and HIV‐D, together with HIV‐1‐infected individuals from the same clinical setting. We assessed important cellular parameters, such as level of immune activation – a marker of disease progression and frequency of cytotoxic T cells (CTL) expressing the effector molecule granzyme B (GrzB), that are reported to confer host cell immunity against viral pathogens . CD4 + T cell subsets such as regulatory T cells (T regs ) (CD25 high CD127 low ), effector memory (CD127 – CD25 – ) and naive/central memory (CD127 + CD25 low/− ), defined on the basis of expression of two important homeostatic markers, interleukin (IL)‐2 receptor (CD25) and IL‐7α receptor (CD127) proposed as targets for immune‐based interventions, were also studied .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast to AGM’s, RM’s experience human AIDS-like diseases during SIV infection such as CD4 T cell depletion, enteropathies, and chronic immune activation, despite high viral loads in both species and similar degrees of antiviral responses [Brenchley and Pairadini 2011, Paiardini et al, 2009]. We previously reported that pathogenic SIV hosts (RM and pigtail macaques) contain more GrzB-expressing CD4 T cells in intestinal tissues compared to non-pathogenic SIV hosts (AGM and sooty mangabeys) [Hutchison et al, 2011]. In the present study of peripheral blood T cells, we further observed differences in GrzB and CCR5 expression, in which RM CD4 T cells expressed more intracellular GrzB than AGM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these differences are unclear, but we found by immunohistochemical analysis of lamina propria from NHP intestinal biopsies that uninfected non-natural SIV hosts (rhesus macaques and pigtail macaques) contain more GrzB-expressing CD4 T cells than natural SIV hosts (African green monkeys and sooty mangabeys) [Hutchison et al, 2011]. This data suggested that GrzB from intestinal CD4 T cells could have a pathological role in pathogenic SIV hosts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above differences, numerous other differences between HIV, SIV, and SHIV and the various strains and clades have been described [1,3,8,21,[27][28][29][30][31][32]39,40,43,44,[52][53][54][55][56][57][58][59]. These differences can be accounted for based the evolutionary trajectories of the viruses including the host-virus interactions.…”
Section: Immunodeficiency Viruses In Humans and Animalsmentioning
confidence: 99%